The Swedish budget 1977/78 - Sweden (Stockholm: Ministry of Finance, 1977)
This fifteenth edition of The Swedish Budget contains a summary of the draft budget for the fiscal year 1977/78, with more detailed reviews of the main items of government expenditure. The budget statement is president in an abbreviated form.
A summary published by the ministry of Finance
rpm 20/02/2019
Ref
Keywords: Budget; Budget; Economic history; Sweden; Sweden